Empirical History of Local Wisdom in Digital Learning Within Islamic Education Management - Permana, Rahayu; Widodo, Widodo (JURNAL AL-TANZIM, 2025)
This study aims to explore the influence of local wisdom on the formation of Islamic character through digital learning among madrasa teachers. This study used a quantitative approach with 285 madrasah teachers as participants. Data were collected using a Likert-scale questionnaire to measure the relevant variables. Partial least squares (PLS)-based structural equation modeling was used in data analysis, along with descriptive and correlational analyses. The results indicate that local wisdom and digital learning influence Islamic character formation. Local wisdom also influences digital learning, which, in turn, mediates its influence on Islamic character formation. Local wisdom has a greater influence on Islamic character formation than digital learning. Therefore, local wisdom deserves greater attention than digital learning in the context of developing Islamic character formation. These findings introduce an empirical model of how local wisdom influences Islamic character formation, mediated by digital learning. This model suggests that digital learning, as a management strategy, can act as a medium for transmitting local wisdom in education and character formation. Thus, its presence needs to be discussed critically before being adopted by researchers for future research and by practitioners, especially in Islamic education management, to optimize the formation of Islamic character based on local wisdom.